EFEK VARIASI JENIS PEMBEBANAN DEFORMASI PLASTIS TERHADAP PERUBAHAN SIFAT MEKANIK DAN STRUKTUR MIKRO PLAT BAJA KARBON - Adri Fato; Margono Sugeng (Bina Teknika, 2020)
Plastic deformation is a permanent deformation that occurs in steel, even though the load causing the deformation is removed. It is widely used to change the shape of steel permanently without adding or reducing the chemical composition of the steel. This permanent change in shape is followed by a change in the shape or phase of the microstructure of the steel. Several types of loading on plastic deformation are Pull (drawing), Stamping and Curling, which are widely used to change the shape of a plate to a curve or a circle.